Comprehensive assessment of insulin resistance in non‐obese Asian Indian and Chinese men. Issue 6 (20th April 2018) - Tan, Hong Chang; Yew, Tong Wei; Chacko, Shaji; Tai, E Shyong; Kovalik, Jean‐Paul; Ching, Jianhong; Myo Thant, Sandi; Khoo, Chin Meng
Abstract: Aims/Introduction: Indian individuals are more insulin resistant (IR) than Chinese individuals, even among those with a non‐obese body mass index (BMI). However, BMI often underestimates body fat in Indian individuals, and it remains unclear whether Indians would remain more IR than Chinese individuals when both BMI and body fat are equally matched. Materials and Methods: Using the hyperinsulinemic‐euglycemic clamp with stable‐isotope infusion, we comprehensively assessed IR between 13 non‐obese Indian men with 13 Chinese men matched for age, BMI and body fat. We further compared the differences in insulin metabolic clearance rate (MCR) between the two groups and its relationship with various metabolic parameters. The response of lipid and amino acid metabolism to insulin stimulation was also evaluated using metabolomic profiling. Results: The rates of endogenous glucose production during fasting were similar, and endogenous glucose production was completely suppressed during insulin clamp for both ethnic groups. Glucose disappearance during insulin clamp was also similar between the two groups, even after accounting for differences in insulin concentration. Metabolomic profiles of amino acids and various acylcarnitines were similar during both fasting and insulin clamp. However, plasma insulin during clamp was significantly higher in Indian men, indicating that insulin MCR was lower. Insulin MCR correlated significantly with total adiposity and skeletal muscle insulin sensitivity. Conclusion: When equally matched for body fat, non‐obese Indian men had similar skeletal muscle insulin sensitivity and endogenous glucose production to Chinese men. The effects of insulin on lipid and amino acid metabolism were also similar. Low insulin MCR is associated with greater adiposity and lower skeletal muscle insulin sensitivity. Abstract : When equally matched for adiposity, non‐obese Asian Indians had the same endogenous glucose production during fasting and insulin clamp.